Postseismic pressure solution creep: Evidence and time‐dependent change from dynamic indenting experiments. Issue 4 (3rd April 2014) - Gratier, Jean Pierre; Renard, François; Vial, Benjamin
Abstract: Active faults in the Earth's upper crust can slide either steadily by aseismic creep or abruptly causing earthquakes. Seismic and aseismic processes are closely related: earthquakes are often followed by transient afterslip creep. Postseismic displacement rates progressively decrease with time over a period of years or decades. So seismic fracturing activates the creep rate, and various healing processes progressively reduce it. This article presents pressure solution indenter experiments on halite, calcite, and plaster that show how fracturing and comminution processes induced by dynamic stress loading (applied by dropping steel balls) drastically accelerate the displacement rates accommodated by pressure solution creep by decreasing the dissolution contact area and the diffusive mass transfer distance along this contact. However, as fractures progressively heal and dissolution contacts flatten, these effects disappear, and the displacement rates slow down. The time‐dependent change in indenter displacement after dynamic stress loading has been measured and is best fitted by power laws with exponents that change with time from 0.3 to 1 when healing is achieved. Natural postseismic (afterslip) displacement/time relationships have been analyzed and also show a power law change with a power law exponent in the range of 0.25–0.4. It is proposed that the variation in power law exponent with time is related to the change in morphology of the dissolution contact that is fractured or comminuted during the dynamic event and is then progressively healed and smoothed. In natural faults, monitoring the power law parameters could give access to the characteristic healing time in the fault. Key Points: What are the mechanisms of postseismic (afterslip) creep How dynamic fracturing accelerates pressure solution creep How healing processes slow down pressure solution creep